2017
DOI: 10.1111/ajt.14258
|View full text |Cite
|
Sign up to set email alerts
|

Filtration Markers, Cardiovascular Disease, Mortality, and Kidney Outcomes in Stable Kidney Transplant Recipients: The FAVORIT Trial

Abstract: Cystatin C and beta-2-microglobulin (B2M) are filtration markers associated with adverse outcomes in non-transplant populations, sometimes with stronger associations than for creatinine. We evaluated associations of estimated glomerular filtration rate from cystatin C (eGFRcys), B2M (eGFRB2M), and creatinine (eGFRcr) with cardiovascular outcomes, mortality, and kidney failure in stable kidney transplant recipients using a case-cohort study nested within the Folic Acid for Vascular Outcome Reduction in Transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…A study by Foster and colleagues demonstrated that estimated GFR (eGFR), calculated from creatinine, cystatin C or β2-microglobulin, is an independent risk factor for cardiovascular events and mortality in RTR [ 49 ]. The highest level of incident cardiovascular disease and all-cause mortality is associated with the lowest eGFR.…”
Section: Non-traditional Cardiovascular Risk Factorsmentioning
confidence: 99%
“…A study by Foster and colleagues demonstrated that estimated GFR (eGFR), calculated from creatinine, cystatin C or β2-microglobulin, is an independent risk factor for cardiovascular events and mortality in RTR [ 49 ]. The highest level of incident cardiovascular disease and all-cause mortality is associated with the lowest eGFR.…”
Section: Non-traditional Cardiovascular Risk Factorsmentioning
confidence: 99%
“…To evaluate the potential association between serum T50 and the composite CVD outcome, we utilized an efficient, preexisting case-cohort selection scheme employed for prior FAVORIT ancillary studies [11][12][13], especially the report of Park et al [13]. Briefly, a 530-participant subcohort with complete baseline data for key laboratory variables, including serum creatinine and lipid studies, as well as urine albumin to creatinine ratio (UACR), was selected at random from the entire cohort, regardless of whether or not the T50, Fetuin-A, and CVD in Kidney Transplantation participants had experienced a fatal or nonfatal CVD outcome during follow-up [11][12][13].…”
Section: Study Populationmentioning
confidence: 99%
“…Briefly, a 530-participant subcohort with complete baseline data for key laboratory variables, including serum creatinine and lipid studies, as well as urine albumin to creatinine ratio (UACR), was selected at random from the entire cohort, regardless of whether or not the T50, Fetuin-A, and CVD in Kidney Transplantation participants had experienced a fatal or nonfatal CVD outcome during follow-up [11][12][13]. We also selected all participants in the full cohort who were identified as having experienced a CVD event, irrespective of whether they were sampled in the random subcohort.…”
Section: Study Populationmentioning
confidence: 99%
“…Data are required from large, well-characterized, multicenter KTR cohorts assessing the potential relationships between serum/plasma, or urinary uromodulin concentrations, and the development of graft failure, as well as CVD outcomes, and all-cause mortality, among chronic, stable KTRs. For example, taking advantage of a powerful, efficient case-cohort design scheme previously used, 42 , 43 the completed FAVORIT clinical trial 44 cohort might be ideally suited to evaluate these associations. One of us (A.B.…”
Section: Uromodulin Quantification In Ktrs: Future Directionsmentioning
confidence: 99%